Implementing English as a Medium of Instruction: Challenges and Benefits - Бортник Світлана Борисівна, Гіков Леонід Вікторович (Одеса : Видавничий дім «Гельветика»., 2024)
The article attempts to analyse some approaches to the use of English as the main language of instruction (EMI) in the system of higher education. The purpose of EMI programs is both to provide students with professional knowledge and to improve English language skills for further global integration. Studies of the EMI phenomenon can be divided into three main groups: studies of language policies and programs, especially in the field of higher education; the research focuses on students, their perceptions and attitudes towards EMI, language and speaking skills, learning strategies, outcomes, and expectations; the third field of research deals with the teachers of higher education and accordingly, how they perceive EMI, the levels of language proficiency and the availability of speaking skills, teaching strategies and procedures, the need for new pedagogical skills are analysed. There are three main models for implementing EMI programs, each of them having its advantages and disadvantages. Experts identify four main types of issues (challenges) that EMI teachers must overcome: teacher's language proficiency, students' language proficiency, acceptable teaching methods, and insufficient resources. Practically all works on the implementation of EMI emphasise the need to improve the language skills of students and teaching staff. Researchers point out a number of advantages for both an individual student and for the university in general, despite all the challenges of EMI implementation. The adoption of the EMI program is not just an automatic move to a different language policy. The implementation of such a method is possible with the joint activity of English language teachers and teachers of professional disciplines - professionals in their field.
Стаття розглядає деякі підходи до використання англійської мови як мови викладання (EMI) фахових предметів на вищому рівні освіти. Головною метою програм EMI є як отримання студентами професійних знань, так і вдосконалення володіння англійською мовою для подальшої глобальної інтеграції.
Keywords: higher education, English for special purposes (ESP), English as medium of instruction (EMI), teacher qualification, code-switching, language training, CLIL (Content and Language Integrated Learning).